2022
DOI: 10.1021/acsestengg.2c00128
|View full text |Cite
|
Sign up to set email alerts
|

Removal and Inactivation of Nonenveloped and Enveloped Virus Surrogates by Conventional Coagulation and Electrocoagulation Using Aluminum and Iron

Abstract: The continued threat of contamination of municipal water supplies necessitates the systematic evaluation of the efficacy of existing unit processes to protect public health and develop new technologies to better attenuate a wide range of viruses in the water we drink. We compared four coagulation approaches (conventional alum and FeCl 3 coagulation and aluminum and iron electrocoagulation) in terms of their ability to remove/inactivate an enveloped virus surrogate (ϕ6) and a nonenveloped virus surrogate (MS2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 70 publications
(165 reference statements)
1
12
0
Order By: Relevance
“…It is noteworthy that the removal and inactivation of Phi6, a model-enveloped virus to respiratory syndrome viruses, were validated in the EF process (Figure S10). A higher level of inactivation of Phi6 than MS2 (3.6 vs 2.4-log) was observed at 30 min, which is in agreement with the previous studies that enveloped viruses are more susceptible to structural damage by oxidation. , …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…It is noteworthy that the removal and inactivation of Phi6, a model-enveloped virus to respiratory syndrome viruses, were validated in the EF process (Figure S10). A higher level of inactivation of Phi6 than MS2 (3.6 vs 2.4-log) was observed at 30 min, which is in agreement with the previous studies that enveloped viruses are more susceptible to structural damage by oxidation. , …”
Section: Resultssupporting
confidence: 92%
“…A recent study reported the EC removal of MS2 and phi6, where 5-log removal required a long residence time of 100–120 min . As a comparison, EF and I-EF showed significantly faster virus removal and inactivation kinetics (residence time <60 min).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…These conditions were chosen because they corresponded to excellent virus attenuation by conventional and electrocoagulation established in previous laboratory studies. 37 After pretreatment, the water was immediately and directly ultrafiltered (i.e., without sedimentation). Note that pH optimization can be a future direction of study because it has been recently recognized as a critical parameter impacting EfOM conformation and system polarity and subsequent fouling.…”
Section: Membranementioning
confidence: 99%